A public relations plan and programs for the University of the Philippines Diliman libraries - Palabrica, Cristina M. (2004)
Library public relations is currently being practiced and encouraged by libraries of all types in many countries throughout the world. It has greatly contributed to the enhancement of the library's image through action programs that aim to establish and maintain a good and cooperative relationship between the library and its diverse clients.